Peramalan Produksi Minyak dan Gas Bumi di Indonesia - Gampar, Yohanes Apriyano; Agustina, Neli (Politeknik Statistika STIS, 2024)
The oil and gas sector remains the primary source of energy in Indonesia. However, the industry faces a significant challenge in declining production year after year. This situation necessitates the implementation of appropriate policies and decisions in oil and gas management to achieve energy security and self-sufficiency through forecasted data. By utilizing forecasting results, it is possible to estimate the realization of the RPJMN targets for oil and gas production for 2023-2024. This study aims to analyze the general trend of Indonesia's oil and gas production from the first quarter of 2007 to the second quarter of 2023, determine the best forecasting model by comparing Holt’s Double Exponential Smoothing and ARIMA methods, and forecast oil and gas production from the third quarter of 2023 to the fourth quarter of 2024 using the best method. The study results indicate a decline in oil and gas production, with an average growth rate of -0.69 percent and -0.48 percent, respectively. Holt's Double Exponential Smoothing is the best method for forecasting oil production, while ARIMA is more suitable for forecasting gas production. The forecast results show a decline in oil production, with an average production of 52,763.19 thousand barrels, and an increase in gas production, with an average production of 493,306.05 MMscf over the next six quarters. This indicates that the oil and gas production targets set by the RPJMN and the Directorate General of Oil and Gas for 2023-2024 have not yet been achieved.